Post-pandemic Office Spaces: : Considerations and Design Strategies for Hybrid Work Environments - Aksamija, Ajla; Milosevic, Suncica (Enquiry The ARCC Journal for Architectural Research, 2023)
This research investigated renovation considerations and design strategies for post-pandemic, hybrid office environment within an academic institution. The focus was on two case-study office spaces that are part of the same organization at the University of Utah, where the existing physical space was insufficient for future growth and non-functional for its novel, hybrid work mode structure. The objective was to evaluate the physical conditions of the existing office spaces, to investigate the employees’ working patterns and office culture, and to propose renovation strategies that would meet both the current and the projected future needs that support a hybrid work structure. The study was based on mixed-mode research methods, which included qualitative and quantitative methods. Qualitative methods included archival and empirical research of the existing office space conditions, as well as users’ input through online survey and focus group interviews. Using the latest, as-built construction drawings and current state photographs, 3D BIM models of each of the two office wings were developed, inclusive of their structural elements, partition walls, existing lighting fixture locations and specific furniture arrangements. These models were then used for egress, circulation, daylighting, and existing space planning analysis. Literature review was also conducted, identifying rising trends and design considerations for hybrid office workflow. Surveys and focus group interviews were conducted with current employees of the two offices to evaluate work patterns and space needs through user insight. Meanwhile, quantitative methods included quantitative analysis of the survey and focus group interview results, computational modeling, and visualization of the existing and proposed design strategies, as well as a review and validation of final design’s egress and accessibility compliance. Through several design option iterations, these results were used to provide space planning strategies and recommendations that meet the specific needs of these two office spaces. The final design, which considered users’ input regarding team dynamics, work schedules, and specific space and function needs, achieved a significant improvement in balances between team and individual space functions, private and public circulation, access to daylight and accessibility, while respecting the existing wall partitions, egress paths and occupancy counts. Moreover, the design solutions provided inclusive, comfortable, and functional spaces that catered to the specific work culture and individualized needs of employees. While this research focused on two specific case-studies, results demonstrate that through a user-integrated approach, significant improvements can be achieved to provide well-functioning spaces and a more comfortable and inclusive working environment. Additionally, the presented process that focuses on user-input and participation in the renovation design process can be applied to other existing, traditionally structured office spaces when transitioning to a hybrid office structure.